Avaliação da proliferação do parênquima pancreático no implante de matriz sintética de poliéter-poliuretano em camundongos - Luciana Xavier Pereira (2017)
The pancreas regenerative ability has been demonstrated in somestudies, but it is no often enough to repair pancreatitis and diabetes lesions. Therefore, animal models of injury have been used for regeneration studies in order to find new strategies to induce pancreas cells proliferation. Alternative approaches in the biomaterials and cell therapy areas have been studied, however, a platform that reconstructs an accurately biological microenvironment has not yet been developed, making clinical application difficult. We implanted a polyether-polyurethane synthetic matrix in interface to the mice pancreas to evaluate the kinetics of induction of the new intra-implant pancreaticparenchyma. Matrix were surgically removed at 15, 30 and 45 days post implant and the components of the pancreas (acini, ducts and islets), blood vessels and inflammatory markers were analyzed. The number of islets and acini were similar, and the number of ducts and vessels were higher inside matrix comparing to the native pancreas. Insulin-positive cells were organized into structures like islets and some ductal cells were positive for insulin. In addition, inflammatory parameters (activity of MPO and NAG and levels of TNF- and CCL2) were higher at day 15 comparing to days 30 and 45 post-implant. To verify if this proliferated pancreatic parenchyma inside implant had metabolic functions, we implanted the scaffold in diabetic animals and later we inoculated it with mesenchymal stem cells derived from human adipose tissue (hASCs), toimprove the response. We evaluated local parameters intra-implant (inflammation, angiogenesis and endocrine cells proliferation) and metabolic parameters of diabetic animals. In the systemic context, we observed that diabetic animals receiving hASCs intra-implant improved glycemic metabolism, C-peptide production and body weight. Locally, diabetic animal implants that received the inoculum of hASCs showed lower inflammatory cytokine content, increased vascularization, and improved endocrine cell proliferation. Our results showed that the matrix was capable of acting as a biological platform for the growth of a new pancreatic parenchyma. Furthermore, because it is easily accessible, it could be explored as a model of pancreatic parenchyma proliferation, being relevant in the understanding of cellular processes that occur in the formation of new tissue.